2018
DOI: 10.1186/s13071-018-3026-y
|View full text |Cite
|
Sign up to set email alerts
|

Is chronic malnutrition associated with an increase in malaria incidence? A cohort study in children aged under 5 years in rural Gambia

Abstract: BackgroundMalnutrition is common in children in sub-Saharan Africa and is thought to increase the risk of infectious diseases, including malaria. The relationship between malnutrition and malaria was examined in a cohort of 6–59 month-old children in rural Gambia, in an area of seasonal malaria transmission. The study used data from a clinical trial in which a cohort of children was established and followed for clinical malaria during the 2011 transmission season. A cross-sectional survey to determine the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…However, several other ethnic groups live in The Gambia, including Fula and Wolof ethic groups [78]. Variability in disease risk and nutrition status between the Fula and the Mandinka ethnic groups has been reported [79]. This finding is consistent with the inter-population genetic variability within African populations, which may also influence differences in disease susceptibility.…”
Section: Plos Onesupporting
confidence: 60%
“…However, several other ethnic groups live in The Gambia, including Fula and Wolof ethic groups [78]. Variability in disease risk and nutrition status between the Fula and the Mandinka ethnic groups has been reported [79]. This finding is consistent with the inter-population genetic variability within African populations, which may also influence differences in disease susceptibility.…”
Section: Plos Onesupporting
confidence: 60%
“…The finding of no association between stuntedness at 6 months and malaria in the subsequent 12-month period is similar to results of previous studies [4245], which suggests that stunting may be of little significance in malaria epidemiology. These results are however different from those of other studies that reported an increased risk of malaria associated with stunting.…”
Section: Discussionsupporting
confidence: 89%
“…Because wealth impacts other indices like education, housing, household nutrition, area of residence and health seeking behaviour, it is arguably a major determinant of U5 malaria (25,27). Although malaria can be rightly described as a disease of poverty (28), no association was found in some studies between chronic malnutrition and U5 malaria (29), suggesting a more complex relationship.…”
Section: Discussionmentioning
confidence: 99%